Improving the Vocabulary Mastery of the Second Year Students’ of MAN 1 Barru by Using Youtube Videos - Putri Melinia Amanda; Ahmad Talib; Mardiyanah Nasta (Journal of Excellence in English Language Education, 2023)
This study aims to determine the results of using Youtube media in improving students' vocabulary mastery in class XI MAN 1 Barru. This research uses the quantitative method. This research is a type of Classroom Action Research. The research data was collected using multiple-choice tests consisting of pre-test and post-test. The sample of this study was cluster random sampling with the assumption that class XI MAN 1 Barru was homogeneous or the same there were 23 students in class XI. The results of this study indicate that there is an increase in students' vocabulary mastery and activities in learning English through the use of Youtube Videos. that the mastery of vocabulary through the use of Youtube videos obtained in cycle I and cycle II there is a significant increase. This increase can be seen by an increase in vocabulary mastery where in the first cycle there are (26.09%) of students have achieved a complete score or score with an average value of 65.07 while in the second cycle, it increases to (100%) of students who have achieved a complete score with an average score of 84.49. This means that it shows an increase in students who get complete scores (73.91%).